1991
DOI: 10.1136/hrt.65.4.194
|View full text |Cite
|
Sign up to set email alerts
|

Diastolic disease in left ventricular hypertrophy: comparison of M mode and Doppler echocardiography for the assessment of rapid ventricular filling.

Abstract: When Doppler and M mode techniques are used to assess rapid filling in patients with left ventricular hypertrophy the M mode indices are more consistently abnormal. The two methods measure different aspects of left ventricular diastolic function and should be regarded as complementary rather than interchangeable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 19 publications
(4 reference statements)
1
12
0
Order By: Relevance
“…These 2 parameters, less popular than Doppler-derived diastolic indices, have been proven more accurate and specific than Doppler parameters in discriminating between normal and abnormal diastole in patients with myocardial hypertrophy. 37 In agreement with previous reports, 1,32,38 we found an impairment of diastolic function in many lean and obese hypertensives, whereas systolic function was normal in all and similar among the 4 groups. To the best of our knowledge, this is the first study testing the hypothesis that genetic predisposition to hypertension can influence the myocardial response to insu- lin, and we think that our results support this hypothesis.…”
Section: Discussionsupporting
confidence: 82%
“…These 2 parameters, less popular than Doppler-derived diastolic indices, have been proven more accurate and specific than Doppler parameters in discriminating between normal and abnormal diastole in patients with myocardial hypertrophy. 37 In agreement with previous reports, 1,32,38 we found an impairment of diastolic function in many lean and obese hypertensives, whereas systolic function was normal in all and similar among the 4 groups. To the best of our knowledge, this is the first study testing the hypothesis that genetic predisposition to hypertension can influence the myocardial response to insu- lin, and we think that our results support this hypothesis.…”
Section: Discussionsupporting
confidence: 82%
“…These indices, less used than Doppler derived parameters, have been demonstrated to be more sensitive in discriminating between normal and impaired diastolic function in the presence of myocardial hypertrophy; they are also less in¯uenced by heart rate and events occurring during isovolumic relaxation. 26 Both diastolic indices were signi®cantly lower in obese than in lean groups. Diastolic dysfunction is a key feature of hypertensive cardiomyopathy, 27,28 but in our young adults obesity appears far more relevant than recently diagnosed hypertension in affecting LV diastolic function: in obese normotensives diastolic indices were signi®cantly lower than in lean hypertensives and, at similar BMI, peak lengthening rate and peak wall thinning rate were only sligthly and not signi®-cantly lower in hypertensives compared with normotensives, despite a signi®cantly greater mass in hypertensives.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they are far less influenced than Doppler indices by age and heart rate. 25 We evaluated also the more often used Doppler-derived diastolic parameters. Many studies showed that a stable and significant BP reduction is associated with regression of myocardial hypertrophy and improvement of LV diastolic function.…”
Section: Discussionmentioning
confidence: 99%